A review of the adoption of renewable energy technologies by hotels in Malawi - Hope Baxter Chamdimba; Emmanuel Mtanila Banda (Journal of Energy in Southern Africa)
The hotel sector is a vital component of the tourism industry, as it plays a critical role in the determination of tourism destination competitiveness. However, lack of reliable, affordable, and sustainable energy supply remains a major bottleneck to the development of the hotel sector in Malawi. The adoption of clean and renewable energy sources around the globe is driven by different factors, such as the need to address environmental challenges and reduce energy costs. Usually, less affordable energy supplies increase the cost of service delivery, thus making these hotels less competitive on the global market. The article investigates the opportunities and barriers to the hotel industry's adoption of renewable energy technologies and includes a literature review. The paper shows that renewable energy technologies have multiple applications in a typical Malawian hotel, and these present numerous economic and environmental opportunities. However, the hotel sector is failing to capitalise on the energy policy and regulation improvements taking place in the country, mainly due to a lack of technological awareness by hotel managers. To reverse this, the government needs to adopt policies and regulations that target the hotel sector to increase awareness and adoption of clean and renewable energy technologies.